Diagnosis and Management of Blastocystis Hominis Infection in Patient with HIV-AIDS - Eka Ginanjar; Agnes Kurniawan; Teguh Hardjono; Ari Fahrial Syam; Ceva Wicaksono Pitoyo (The Indonesian Society for Digestive Endoscopy, 2007)
The incidence of AIDS/HIV infection has been increasing worldwide. Patients with AIDS/HIV infection is at high risk to get opportunistic infection which is often become life-threatening. Common infections associated with AIDS/HIV are tuberculosis (TB) infection and viral hepatitis. Commensal organism found in human body is actually not pathogenic. Blastocystis hominis is generally considered as commensal organism of intestinal tract and might cause opportunistic infection in patients with AIDS. We reported a case of young male patient with AIDS/HIV infection and evidence of opportunistic infection of Blastocystis hominis found in ascitic fluid along with concomitant lung TB and viral hepatitis. Patient was well-responded to treatment of B. Hominis. Keywords: AIDS/HIV infection, opportunistic infection, Blastocystis hominis